2015
DOI: 10.1103/physrevlett.114.114301
|View full text |Cite
|
Sign up to set email alerts
|

Topological Acoustics

Abstract: The manipulation of acoustic wave propagation in fluids has numerous applications, including some in everyday life. Acoustic technologies frequently develop in tandem with optics, using shared concepts such as waveguiding and metamedia. It is thus noteworthy that an entirely novel class of electromagnetic waves, known as "topological edge states," has recently been demonstrated. These are inspired by the electronic edge states occurring in topological insulators, and possess a striking and technologically prom… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
837
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,209 publications
(865 citation statements)
references
References 27 publications
(34 reference statements)
2
837
1
1
Order By: Relevance
“…Fundamental research in systems where timereversal symmetry is broken have been found to support unidirectional edge modes that remain intact over long distance and against defects; these systems include magneto-optics [1,2], photonics [3][4][5] and acoustics [6]. While these systems have very different underlying physics they all share some common properties; they have a boundary that separates two distinct regions.…”
Section: Introductionmentioning
confidence: 99%
“…Fundamental research in systems where timereversal symmetry is broken have been found to support unidirectional edge modes that remain intact over long distance and against defects; these systems include magneto-optics [1,2], photonics [3][4][5] and acoustics [6]. While these systems have very different underlying physics they all share some common properties; they have a boundary that separates two distinct regions.…”
Section: Introductionmentioning
confidence: 99%
“…From an experimental perspective, these systems appear to be well within reach since either in the realm of beads [51,52], or even in the more recent setup of magnets [56], it should be possible to construct a system tantamount to the one considered here, bearing in mind the considerable insights that their optical (even linear) analogues have offered; for a recent example, see [57]. Finally, this realization, in turn, would pave the way for additional intriguing features such as potential acoustic realizations [58] of topological edge states cf. [59][60][61][62], among others.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…Topological states have also been extended to condensed-matter physics based on the quantum Hall effect (QHE) [1,2], the quantum spin Hall effect (QSHE) [3,4], and topological insulators (TIs) [5,6]. Over the past ten years, investigation into new topologically protected edge states has started to grow in other subfields of physics, such as photonics [7][8][9][10][11][12][13][14][15][16], phononics [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32], and mechanics [33][34][35][36]. The intrinsic difference between electrons and acoustic waves represents a great challenge in creating the spinlike degree of freedom for sound only possessing longitudinal polarization.…”
mentioning
confidence: 99%